Evaluación de patrones de aguacate (Persea americana M.), en cuatro ecotipos nacionales con diferentes sustratos, en condiciones de invernadero - Quiña Morales, Cristian Víctor (2018)
VII. SUMMARY In this research the evaluation of patterns avocado was performed in four national varieties with different substrates under greenhouse conditions Designing Complete Random Blocks (was used factorial arrangement combined, specific treatments will be giving a total of 12 treatments and three replications, a total of 36 units The variables were evaluated: germination percentage, height pattern (30-60 ddg), stem diameter (30-60) percentage of surviving grafts, buds size, number of leaves per shoot and treatments were economically analyzed . The averages obtained in the variables were subjected to the sensitivity test Duncan 5% probability for statistical differences between the means of the factors the experimental results showed that: the highest average in the percentage of germination Green pear variety and more leaves sprout. In the substrates showed better results in height patterns, percentage of surviving grafts, size of sprouts and number of leaves per shoot, being statistically equal to the mixture of as a percentage of engraftment grafts and size of outbreak, treatment obtained higher averages germination percentage, height patterns, percentage of engraftment of grafts, number of leaves per shoot, statistically similar to treatment of all varieties with substrates in assessing patterns height, percentage of surviving grafts, economic analysis Mostros in all treatments was presented economic utility; They obtain most useful treatments and recorded the highest economic profit with $ 10,216.00.